Influence of serum testosterone on urinary continence and sexual activity in patients undergoing radical prostatectomy for clinically localized prostate cancer - Gacci, M; Corona, G; Apolone, A; Lanciotti, M; Tosi, N; Giancane, S; Masieri, L; Serni, S; Maggi, M; Carini, M (Prostate cancer and prostatic diseases, 2010)
The aim of the present study was to evaluate how serum testosterone level ( T ) can affect urinary continence and erectile function in patients undergoing radical prostatectomy (RP). We included 257 patients with clinically localized prostate cancer, those who had filled out preoperative quality of life questionnaires (University of California, Los Angeles Prostate Cancer Index, International Index of Erectile Function (IIEF)), and those who had T and total PSA sampled the day before surgery. We calculated correlations between T and age, body mass index (BMI), PSA, urinary function or bother (UF, UB) and sexual function or bother (SF, SB) and IIEF-5 in the whole population and in sub-populations with normal (⩾10.4 nmol l −1 ) and low (<10.4 ng ml −1 ) T using Pearson's and Spearman's correlation coefficients. We evaluated differences in these parameters between patients with low and normal T using the unpaired samples t -test and Mann–Whitney test, and finally the correlation between UF and SF, UB and SB, and between PSA and T in the overall population, and separately in patients with low and normal T using the Pearson's correlation coefficient. Mean preoperative T was 13.5 nmol l −1 and 23.7% of patients presented a low T . Mean age, mean BMI and mean preoperative total PSA at RP were 64.3 years, 25.9 kg m −2 and 9.0 ng ml −1 , respectively. BMI was negatively correlated with T in the overall population ( r =−0.266; P =0.02); moreover, patients with normal T presented lower BMI compared with patients with low T (25.7 vs 27.6: P =0.02). We found a significant correlation between SF scores and T in patients with normal T ( r =0.1777: P =0.05). SF was significantly higher in patients with normal T compared with those with low T (74.8 vs 64.8: P =0.05). Furthermore, UF and UB were significantly correlated with SF ( r =0.2544: P <0.01) and SB ( r =0.2512: P =0.01), respectively, in men with normal T . Serum T was significantly correlated with PSA in men with low T ( r =0.3874: P =0.0029), whereas this correlation was missed in the whole population and in men with normal T . The correlation between preoperative PSA and T in men with low T is in agreement with the ‘saturation’ model proposed by Morgentaler. The correlation between basal T and preoperative erectile function and urinary continence underlines the importance of assessing T before RP.